Play Manners Education: A Storytelling Video For Autistic Children - Maisarah Saidin; Nur Fatimatul Insyirah Shamsudin; Nur Shafika Arifin; Muhammad Nassem Mohamed Ghazali (Universiti Sains Islam Malaysia, 2025)
Journal of Quran Sunnah Education & Special Needs, Volume 8 Issue 2 Page (49-66)